1991
DOI: 10.1097/00000658-199109000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-year Experience With Aortic Root Replacement

Abstract: During a 16-year interval ending in October 1990, 168 patients underwent 172 aortic root replacements. Thirty patients (18%) had Marfan syndrome. Annuloaortic ectasia (81 patients) and aortic dissection (63 patients) were the principal indications for operation. Twenty-seven patients (16%) had previous operations on the ascending aorta or aortic valve. The hospital mortality rate was 5% and the duration of cardiopulmonary bypass was the only significant independent predictor of early death (p = 0.017). Major m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
2
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(232 citation statements)
references
References 30 publications
9
212
2
9
Order By: Relevance
“…Operative techniques have been well described in previous publications for the classic Bentall procedure, 4 the modified Bentall procedure, 8 the Yacoub remodeling valve-preserving aortic root reconstruction, 9 and the David reimplantation valve-preserving aortic root reconstruction. 10 Operative procedures performed are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Operative techniques have been well described in previous publications for the classic Bentall procedure, 4 the modified Bentall procedure, 8 the Yacoub remodeling valve-preserving aortic root reconstruction, 9 and the David reimplantation valve-preserving aortic root reconstruction. 10 Operative procedures performed are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] In an attempt to avoid anticoagulation in this relatively young patient population, Sarsam and Yacoub 9 and David and Feindel 10 have described valve-preserving aortic root reconstruction techniques. Despite the fact that the valve cusps often appear functionally normal, there is evidence that they have abnormalities similar to those in the aortic wall tissue, [11][12][13] potentially limiting their durability.…”
mentioning
confidence: 99%
“…The patients underwent aortic root reconstruction using a composed valvulated tube according to the technical variations of the Bentall operation [4] ("Button Bentall"). The lesioned segment of the ascending aorta and the aortic valve were replaced by a Dacron tube and a mechanical or biological valve, respectively.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In the years since, this technique has gone through several modifications [4] and has become the procedure of choice for the treatment of aortic valve disease associated with the involvement of the ascending aorta. Study results with long-term follow-ups of patients who underwent this procedure showed good results with this technique [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A significativa incidência de pseudo-aneurismas tardios, associada à dificuldade do reimplante direto das coronárias, em casos de dilatação não muito importante dos seios de Valsalva, sustentam a modificação proposta por Kouchoukos e cols., 13 na qual os óstios coronarianos são excisados e implantados no tubo sob a forma de botões; esta técnica, denominada button Bentall, tem apresentado baixa mortalidade hospitalar e menor probabilidade de eventos tardios [14][15][16] . Alternativamente, a modificação proposta por Cabrol e cols., 17 em que um segmento de PTFE é conectado à porção ascendente do tubo de dacron, anastomosada aos óstios coronarianos, de modo término-terminal, pode ser útil em pacientes idosos, ou em casos em que há necessidade de reconstrução muito complexa dos demais segmentos da aorta torácica.…”
Section: Dissecções Agudas Da Aortaunclassified